Modularly engineered injectable hybrid hydrogels based on protein-polymer network as potent immunologic adjuvant in vivo. (March 2019) - Giang Phan, V.H.; Duong, Huu Thuy Trang; Thambi, Thavasyappan; Nguyen, Thanh Loc; Turabee, Md. Hasan; Yin, Yue; Kim, Seong Han; Kim, Jaeyun; Jeong, Ji Hoon; Lee, Doo Sung
Abstract: Lymphoid organs, which are populated by dendritic cells (DCs), are highly specialized tissues and provide an ideal microenvironment for T-cell priming. However, intramuscular or subcutaneous delivery of vaccine to DCs, a subset of antigen-presenting cells, has failed to stimulate optimal immune response for effective vaccination and need for adjuvants to induce immune response. To address this issue, we developed an in situ-forming injectable hybrid hydrogel that spontaneously assemble into microporous network upon subcutaneous administration, which provide a cellular niche to host immune cells, including DCs. In situ-forming injectable hybrid hydrogelators, composed of protein-polymer conjugates, formed a hydrogel depot at the close proximity to the dermis, resulting in a rapid migration of immune cells to the hydrogel boundary and infiltration to the microporous network. The biocompatibility of the watery microporous network allows recruitment of DCs without a DC enhancement factor, which was significantly higher than that of traditional hydrogel releasing chemoattractants, granulocyte-macrophage colony-stimulating factor. Owing to the sustained degradation of microporous hydrogel network, DNA vaccine release can be sustained, and the recruitment of DCs and their homing to lymph node can be modulated. Furthermore, immunization of a vaccine encoding amyloid-β fusion proteinbearing microporous network induced a robust antigen-specific immune response in vivo and strong recall immune response was exhibited due to immunogenic memory. These hybrid hydrogels can be administered in a minimally invasive manner using hypodermic needle, bypassing the need for cytokine or DC enhancement factor and provide niche to host immune cells. These findings highlight the potential of hybrid hydrogels that may serve as a simple, yet multifunctional, platform for DNA vaccine delivery to modulate immune response.